2010
DOI: 10.1523/jneurosci.0402-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Excess Phosphoinositide 3-Kinase Subunit Synthesis and Activity as a Novel Therapeutic Target in Fragile X Syndrome

Abstract: Fragile X syndrome (FXS) is an inherited neurologic disease caused by loss of fragile X mental retardation protein (FMRP), which is hypothesized to mediate negative regulation of mRNA translation at synapses. A prominent feature of FXS animal models is exaggerated signaling through group 1 metabotropic glutamate receptors (gp1 mGluRs), and therapeutic strategies to treat FXS are targeted mainly at gp1 mGluRs. Recent studies, however, indicate that a variety of receptor-mediated signal transduction pathways are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
284
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(303 citation statements)
references
References 56 publications
(117 reference statements)
15
284
3
1
Order By: Relevance
“…FMRP was shown to repress translation of individual target mRNAs as well as general protein synthesis (Zalfa et al, 2003;Lu et al, 2004;Dolen et al, 2007;Muddashetty et al, 2007;Gross et al, 2010;Osterweil et al, 2010). On the other hand, recent work suggests that FMRP can also act as a translational activator for specific target mRNAs (Bechara et al, 2009;Fahling et al, 2009;Gross et al, 2011).…”
Section: Fmrp: a Key Regulator Of Neuronal Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…FMRP was shown to repress translation of individual target mRNAs as well as general protein synthesis (Zalfa et al, 2003;Lu et al, 2004;Dolen et al, 2007;Muddashetty et al, 2007;Gross et al, 2010;Osterweil et al, 2010). On the other hand, recent work suggests that FMRP can also act as a translational activator for specific target mRNAs (Bechara et al, 2009;Fahling et al, 2009;Gross et al, 2011).…”
Section: Fmrp: a Key Regulator Of Neuronal Functionmentioning
confidence: 99%
“…They include in vivo and in vitro studies, as well as analyses of dendritic protrusion and filopodia density, dendritic spine classification, and dendritic arborization (see, eg, McKinney et al, 2005;de Vrij et al, 2008;Gross et al, 2010;Grossman et al, 2010). Some findings are contradictory; for example, several studies have reported significantly increased total dendritic spine density in cultured hippocampal Fmr1 KO neurons as well as in cortex and olfactorial bulb in vivo (Hayashi et al, 2007;Gross et al, 2010;Liu et al, 2011;Scotto-Lomassese et al, 2011), whereas other studies have detected increased numbers of filopodia, but no significant difference in total spine density in the cortex in vivo and in cultured hippocampal neurons (Irwin et al, 2002;de Vrij et al, 2008;Bilousova et al, 2009). Different experimental settings, such as age of the mice or neuronal cultures, might explain variations in the observed phenotypes.…”
Section: Abnormal Dendritic Spine Morphology In Fxsmentioning
confidence: 99%
See 2 more Smart Citations
“…mGluR1/5 links via Homer to PIKE (PI3 kinase enhancer) at synapses, where it engages PI3K-mTOR signaling in response to synaptic stimulation. PIKE, an upstream activator of mTOR and identified target of FMRP (Darnell et al, 2011) is elevated at the synapses of Fmr1 KO mice (Gross et al, 2010;Sharma et al, 2010), providing a functional link between loss of FMRP and overactivated mTOR signaling (Figure 1). These findings identify dysregulation of mTOR signaling as a phenotypic feature common to FXS, TSC1 and 2, NF1, and PTEN-associated autism syndromes.…”
Section: David Feifelmentioning
confidence: 99%